KAJI EKSPERIMENTAL DAN NUMERIK TENTAN G FAKTOR KETANGGUHAN RETAK MODUS I DAN II PADA LAMINATE KARBON/EPOXY SERAT TERANYAM - IGN Wiratmaja Puja; Rochim Suratman; Aditianto Ramelan; Hariadi Tri Prasetia (Mesin, 2000)
This paper presents experimental and numerical analysis on the inï¬‚uence of crack orientations to the fracture toughness of mode I and mode II for woven type carbon/epoxy four ply laminate. The experimental procedure is carried out through off axis tensile test (ASTM D 3039-76) with nine variation of crack orientations i.e. 5°, 10°, 15°, 30°, 45° 65°, 75°, 80°, and 90°. Three rail shear test (ASTM D 4255-83) is utilized for zero degree crack orientation. The stress and strain contours around crack tips are obtained numerically using the ï¬nite element method. Numerical and experimental results of the mode I (KI) and mode II (KII) fracture thoughness are presented in graphical form as a function of crack directions. Adopting Wu's(11) Criteria for unidirectional lamina and Hahn's[6] Criteria for general anisotropic lamina, a new mixed mode fracture toughness criteria is developed for woven ï¬ber matrix laminate.